Mind the gap! A survey comparing current strength training methods used in men`s versus women`s first team and academy soccer - McQuilliam, S. J.; Clark, D. R.; Erskine, R. M.; Brownlee, T. E. (Science and Medicine in Football, 2022)
Purpose: Much less is known about strength and conditioning (S&C) practice in women`s versus men`s soccer. The aim of this study was to compare S&C practice between coaches working in men`s or women`s soccer, at first team or academy level, worldwide. Methods: A total of 170 participants, who were involved with S&C support at their soccer club (in Europe, USA and South America, within men`s or women`s first team or academy settings) completed a comprehensive online survey, designed to evaluate (i) their academic qualifications and S&C coaching experience; and their preferred methods for (ii) physical testing; (iii) strength and power development; (iv) plyometric training; (v) speed development; and (vi) periodization. Results: Women`s academies had fewer weekly in-season S&C sessions than men`s academies (1.6±0.6 vs. 2.3±0.9, p=0.005). Relatively, fewer women`s academy S&C coaches (6%) used Olympic weightlifting movements than men`s academy S&C coaches (32%, p=0.030). Relatively, more women`s academy coaches (47%) used the Nordic hamstring exercise (NHE) compared to men`s academy coaches (15%, p=0.006), but relatively more women`s vs. men`s first team coaches (61% vs. 38%, p=0.028) and women`s vs. men`s academy (61% vs. 38% coaches, p=0.049) utilised rating of perceived exertion-based load prescriptions. Conclusion: Notable differences in S&C practice exist between coaches of men`s and women`s soccer squads, particularly at academy level. Fewer weekly S&C sessions in women academy players may have implications for physical development, while the greater use of subjective load prescriptions in both academy and first team women`s squads may lead to sub-optimal performance gains.